2021
DOI: 10.1038/s41598-021-83580-8
|View full text |Cite
|
Sign up to set email alerts
|

Antagonist effects of the leek Allium porrum as a companion plant on aphid host plant colonization

Abstract: Combining a non-host plant (companion plant or CP) with a target cultivated plant is considered as a promising strategy to reduce pest pressure. Among the companion plants (CP) commonly used in integrated systems, those belonging to the Amaryllidaceae family (chives, garlic, onion, leek) exhibit characteristics related to certain volatile organic compounds (VOCs) with promising repellent potentialities. The aim of this work was to investigate the potential disruption of sweet pepper (host plant) colonization b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
2
6
0
Order By: Relevance
“…Our study also showed that the repellency of the rubber septum filled with garlic EO was counterbalanced by the attractiveness of the host plant (HP + EO vs. blank), as no preference between the two sources and no difference in latency time was observed. This is consistent with the study of Baudry et al (2021), who showed that although M. persicae was attracted by VOCs of sweet pepper (Capsicum annuum L.) and repelled by leek (Allium T A B L E 3 Mean (± SEM; n indicates sample sizes) feeding behavior parameters of pear psyllid on pear depending on the rubber septum associated with the plant, either filled with ethanol (control) or containing garlic essential oil (EO) porrum L.), combination of those odors was neither repellent nor attractive to M. persicae. Similarly, garlic chive (A. tuberosum) and wild onion (Allium canadense L.) volatiles affect the attractiveness of D. citri towards volatiles of its host plant Citrus spp.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our study also showed that the repellency of the rubber septum filled with garlic EO was counterbalanced by the attractiveness of the host plant (HP + EO vs. blank), as no preference between the two sources and no difference in latency time was observed. This is consistent with the study of Baudry et al (2021), who showed that although M. persicae was attracted by VOCs of sweet pepper (Capsicum annuum L.) and repelled by leek (Allium T A B L E 3 Mean (± SEM; n indicates sample sizes) feeding behavior parameters of pear psyllid on pear depending on the rubber septum associated with the plant, either filled with ethanol (control) or containing garlic essential oil (EO) porrum L.), combination of those odors was neither repellent nor attractive to M. persicae. Similarly, garlic chive (A. tuberosum) and wild onion (Allium canadense L.) volatiles affect the attractiveness of D. citri towards volatiles of its host plant Citrus spp.…”
Section: Discussionsupporting
confidence: 94%
“…This is in accordance with a study of M. persicae feeding behavior on Tanacetum vulgare L. sprayed with Allium cepa L. (onion) extracts (Dancewicz et al, 2011), showing post-ingestion deterrent activity previously defined by Chyb et al (1995). Similar disruption (decreased phloem sap ingestion) was shown in aphid host plant acceptance caused by leek as a companion plant (Baudry et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the insect repellency increased with increased concentrations, irrespective of the extracting solvent. A recent study showed mixed effects of leek as a companion plant on aphid (Myzus persicae) colonisation of sweet pepper (Capsicum annuum L.); whilst the volatile compounds of leeks had a negative effect on aphids' feeding behaviour, no effect was observed on the orientation of the aphids (Baudry et al 2021). Some of the compounds identified in leeks in this study have repellent activities; for example, dimethyl trisulfide can repel the red spider mite Tetranychus urticae (Hincapié, López & Torres et al 2008).…”
Section: Discussionmentioning
confidence: 48%
“…However, the time to initiate a probe was the shortest on apigenin-treated plants in relation to other flavonoid treatments. Nevertheless, it is typical for aphids to start probing in a few minutes' time after access to their host plants if no repellent factors are present [62][63][64][65]. The initiation of stylet penetration by aphids in EPG experiments may be affected by a variety of internal and external factors, such as plant surface features including color, texture and phytochemicals (volatile and nonvolatile) [62].…”
Section: Discussionmentioning
confidence: 99%